Evaluation of the contribution of Small and Medium Enterprises (SMEs) to the economic development of Algeria: Statistical study on the period 2002-2020. - عميمر عمر; خزار رمضان (khazzartech الاقتصاد الصناعي, 2023)
The goal of this study is to quantify the contribution of newly created small and medium-sized enterprises (SMEs) to expected socioeconomic development and to better understand the relationship between SMEs and that development through an analysis of their contribution to job creation, non-hydrocarbon exports, and gross domestic product. To this end, we conducted a statistical study on the evolution of the parameters studied during the period between 2002 and 2020, which showed us the importance of SMEs, which have recorded a continuous evolution, in the creation of jobs and wealth illustrated by the share of the added value of SMEs in the gross domestic product (GDP). The study showed us, moreover, that the share of SMEs in exports remains insignificant, which testifies to the dependence of the Algerian economy on hydrocarbon exports.